1996
DOI: 10.1002/(sici)1097-010x(19960101)274:1<1::aid-jez1>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Physiological adaptations of rainbow trout to chronically elevated water pH (pH = 9.5)

Abstract: Recent investigations have demonstrated that rainbow trout cope with acute high pH (pH > 9.0) exposure (lasting 3–8 days) through their ability to counteract high‐pH‐induced disturbances to ammonia excretion (JAmm), acid‐base homeostasis, and electrolyte balance. In the present investigation our goal was to establish how these physiological processes were modulated during chronic (28‐day) high pH (pH = 9.5) exposure. Chronic high pH led to minimal mortality, and there were no long‐term changes in stress indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 54 publications
1
6
0
1
Order By: Relevance
“…Total ammonia and urea concentrations in the water were determined as described by Wilkie et al (1996). Plasma ammonia was determined enzymatically (GDH), using a commercial kit (Sigma).…”
Section: Nitrogenous Waste and Metabolite Analysesmentioning
confidence: 99%
“…Total ammonia and urea concentrations in the water were determined as described by Wilkie et al (1996). Plasma ammonia was determined enzymatically (GDH), using a commercial kit (Sigma).…”
Section: Nitrogenous Waste and Metabolite Analysesmentioning
confidence: 99%
“…Levi et al, 1974), because the increases in urea excretion were relatively modest. Similar declines in urea were reported in the muscle of rainbow trout exposed to alkaline water (Wilkie et al, 1996), and in the plasma of Atlantic salmon (Salmo salar) exposed to ammonia (Knoph and Thorud, 1996). It seems unlikely that the unloading of such relatively modest amounts of urea by ammoniaexposed goldfish would play a role in ammonia detoxification given the 10-20-fold higher concentrations of ammonia in the muscle of the fish at HEA.…”
Section: Effects Of Hea On Muscle Nitrogen Stores and Urea Excretion mentioning
confidence: 99%
“…For this reason, data for the two receptor types were pooled for the second experiment. Chemically responsive receptors did not respond to any of the innocuous chemicals -alarm pheromone, ammonium chloride, bile, freshwater and sodium bicarbonate (Holliman, 1993;Hara, 1994;Sorensen and Caprio, 1998;Craig and Laming, 2004;Galea, 2002;Wilkie et al, 1996) -suggesting that they have a purely nociceptive function. These mechanochemical receptors responded to between one and five (all of the potentially noxious agents tested) types of agent.…”
Section: Discussionmentioning
confidence: 65%
“…Ammonium chloride at high concentrations is toxic to teleosts, but concentrations between 0.02 and 1.0mgl -1 were tested -levels that are assumed to be non-irritating to trout (Hedtke and Norris, 1980;Holliman, 1993;Saha and Ratha, 1994;Craig and Laming, 2004). Sodium bicarbonate was also tested (at 0.1, 0.5 and 1.0moll -1 ) because alkaline waters can have deleterious effects on fish physiology but several studies have shown that rainbow trout can adapt and survive in high pH environments, an event that can occur naturally in eutrophic lakes (Yesaki and Iwama, 1992;Wilkie and Wood, 1994;Wilkie et al, 1996). High pH has not been reported to excite nociceptors in other vertebrates (Galea, 2002;Woolf and Ma, 2007;Dafny, 2010).…”
Section: Chemosensitive Receptor Responses To Different Agentsmentioning
confidence: 99%